The Influence of the Sympathetic Nervous System on Cardiometabolic Health in Response to Weight Gain or Weight Loss - Gavin W. Lambert; Mariya Patel; Elisabeth A. Lambert (Metabolites)
Alterations in sympathetic nervous activity are evident in response to changes in body weight. Sympathetic nervous activity and sympathetic responses to weight change are regionalized, with alterations in end organ function dependent on the changes occurring in the brain regulatory pathways invoked and in the effector organs engaged. The obesity-induced activation of the sympathetic nervous system likely contributes to the initiation and worsening of cardiometabolic risk factors, including elevated blood pressure, cardiac dysfunction, dyslipidaemia, increased fasting blood glucose, insulin resistance, and non-alcoholic steatohepatitis. Unintended weight loss, as occurs in cachexia, is driven, at least in part, by the activation of sympathetic nervous-stimulated thermogenesis. The complexity of sympathetic nervous regulation renders the use of global measures of sympathetic activity problematic and the development of targeted therapies difficult, but these are not without promise or precedent. Knowledge of the central and peripheral pathways involved in sympathetic nervous regulation has opened up opportunities for pharmacological, surgical, and device-based approaches to mitigating the burden of disease development and progression. In this narrative review, we elaborate on sympathetic activity in response to changes in body weight, the brain pathways involved, and the cardiovascular and metabolic risks associated with perturbations in regional sympathetic activity.